Applying the Benefit Theory to Strengthen Public Protection in Marriage Record-Keeping - -, Maulana; Yumarni, Ani; Suryani, Danu (Sultan Agung Notary Law Review, 2025)
The Benefit Theory is a guarantee of quality of life for people who obey religion because it is an Islamic command that comes from the Koran and hadith for the public good. Marriage is a spiritual and physical bond between a man and a woman to become husband and wife and has the aim of building a happy, harmonious and mutually loving household. Underhand marriage is a condition where it is not registered at the KUA religious affairs office or agency in accordance with the law. Recording important events according to law number 24 of 2013 concerning amendments to law number 23 of 2006 states that recording important events are events experienced by a person including birth, death, stillbirth, name changes and changes in citizenship status. The population administration law is a manifestation of the state's attention to its citizens. Every incident is recorded in order to obtain equality or equality before the law. There are many legal consequences for illegal marriages if they do not comply with population administration laws because there is no legality of marriage recognized by the state in the form of a Marriage Certificate.